2019
DOI: 10.1590/0001-3765201920190434
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B6 reduces oxidative stress in lungs and liver in experimental sepsis

Abstract: Sepsis is a life-threatening organ dysfunction induced by a disrupted host response to infecting pathogens. Inflammation and oxidative stress are intrinsically related to sepsis progression and organ failure. Vitamin B6 is an important cellular cofactor for metabolic processes and has anti-inflammatory and antioxidant properties. We aimed at evaluating the effect of vit B6 on inflammation and oxidative stress markers in the liver and lung of rats subjected to a relevant animal model of polymicrobial sepsis. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Similar to immune cells, liver cells increase ROS production during sepsis 49,50 . We offer a potential mechanism whereby sepsis leads to significant depletion of redox metabolites within the glutathione pathway ultimately culminating in loss of cellular glutathione levels resulting in ophthalamate accumulation in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to immune cells, liver cells increase ROS production during sepsis 49,50 . We offer a potential mechanism whereby sepsis leads to significant depletion of redox metabolites within the glutathione pathway ultimately culminating in loss of cellular glutathione levels resulting in ophthalamate accumulation in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In LPS‐induced acute pneumonia, vitamin B6 down‐regulates the inflammatory gene expressions by increasing AMP‐activated protein kinase phosphorylation 15 . In experimental sepsis, vitamin B6 reduces oxidative stress in the lungs and liver 16 . Nevertheless, the exact mechanism of the anti‐inflammatory role of vitamin B6 is still unclear and needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been previously demonstrated that the administration of vitamin B-6 (100 mg/kg) considerably ameliorated the chromium-induced oxidative stress in rats [29]. Indeed, the administration of a single dose of vitamin B-6 (600 mg/kg, subcutaneous) immediately into cecal ligation and perforation-induced mid-grade septic rats could remarkably reduce acute oxidative damage in the liver [30]. Since Horowitz et al suggested an impaired transsulfuration pathway in cirrhosis patients [31], we speculated that the antioxidant properties of vitamin B-6 might be deranged or blocked in cirrhosis, even though the plasma PLP levels increased following a large dose of vitamin B-6 supplementation.…”
Section: Discussionmentioning
confidence: 98%